(untitled) (Applied Biological Research, 2015)
Line x tester analysis over environments was carried out in rice during 2011 and 2012, with 9 lines, 3 testers and 27 hybrids thus generated. Analysis of variance revealed significant differences among genotypes for most of the characters studied. Mean squares due to G x E interaction and environmental component was observed to be significant for all the traits. Analysis of variance further revealed significant mean squares for general and specific combining ability for all traits. The mean sum of squares due to environments was also significant for most of the traits. The variances of SCA were higher than GCA variances for some of the characters but reverse was true for other characters, thus showing importance of both additive and non-additive genetic components. The GCA estimates for grain yield plant-1 suggested that the parents ‘K-08-60’, ‘K-08-61’ and ‘Pusa Sugand-5’ as promising on the basis of significant positive GCA effects at pooled levels.